2015
DOI: 10.1136/bjsports-2015-095586
|View full text |Cite
|
Sign up to set email alerts
|

The psychological response to injury in student athletes: a narrative review with a focus on mental health

Abstract: BackgroundInjury is a major stressor for athletes and one that can pose significant challenges. Student athletes must handle rigorous academic as well as athletic demands that require time as well as significant physical requirements. Trying to perform and succeed in the classroom and on the playing field has become more difficult as the demands and expectations have increased. If an athlete is injured, these stressors increase.Main thesisStress is an important antecedent to injuries and can play a role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 58 publications
3
166
2
7
Order By: Relevance
“…To note, PTS in our study was reported with a significantly higher frequency compared to other pain responses, such as magnification, the interpretation of pain as a sign of a serious condition or as help‐/hopelessness. These results are in line with previous reports of high‐performance athletes who most often tend to ignore their pain in order to focus on the competition (Deroche et al, ; Nixon, ; Putukian, ). Although “ignoring pain” may conceptually not be identical with PTS, we can suppose that athletes very often attempt to divert their attention away from pain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To note, PTS in our study was reported with a significantly higher frequency compared to other pain responses, such as magnification, the interpretation of pain as a sign of a serious condition or as help‐/hopelessness. These results are in line with previous reports of high‐performance athletes who most often tend to ignore their pain in order to focus on the competition (Deroche et al, ; Nixon, ; Putukian, ). Although “ignoring pain” may conceptually not be identical with PTS, we can suppose that athletes very often attempt to divert their attention away from pain.…”
Section: Discussionsupporting
confidence: 92%
“…Athletes, particularly in high-level competitive sports, are socialized to ignore pain (Deroche, Woodman, Stephan, Brewer, & Scanff, 2011;Nixon, 1993;Putukian, 2016) in order to function in competition. However, not much research has been carried out yet in athletes on habitual TS with regard to pain that occurs outside competition or performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, some responses can trigger more serious psychological issues including anxiety, depression, substance abuse and eating disorders. It Paralympic athletes' perceptions of their experiences 7 is therefore important for clinicians, as well as trainers and coaches, to recognise common symptoms and signs and to provide support for injured athletes (Putukian, 2016). Based on these findings it is recommended that actions are taken to support and to educate athletes, trainers and coaches how to manage SRIP and the psychological stressors that may arise.…”
Section: The Consequences Of Sripmentioning
confidence: 99%
“…Bearing in mind that men with prostate cancer undergoing androgen deprivation therapy have a quadruple risk of bone fractures (López et al, 2005), the known risk of football injuries could well constitute a significant barrier in clinical referral and implementation of the program. Moreover, from the sport psychology literature, we know that sports injuries can be difficult to overcome and may lead to isolation and considerable psychological distress (Covassin, Beidler, Ostrowski, & Wallace, 2015;Putukian, 2016). Most research on sports injuries, however, involve young professional athletes in competitive sport (Christakou & Lavallee, 2009;Drummond, 2002;Podlog, Heil, & Schulte, 2014), whereas the psychological response to injuries sustained in recreational sport in nonprofessionals, especially in older people, is poorly understood.…”
mentioning
confidence: 99%